2017
DOI: 10.1002/jnr.24027
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase‐A and B activities in the cerebellum and frontal cortex of children and young adults with autism

Abstract: Monoamine oxidases (MAOs) catalyze the metabolism of monoamine neurotransmitters, such as serotonin, dopamine, and norepinephrine, and are key regulators for brain function. In this study, we analyzed the activities of MAO-A and MAO-B in the cerebellum and frontal cortex from subjects with autism and age-matched control subjects. In the cerebellum, MAO-A activity in subjects with autism (aged 4-38 years) was significantly lower by 20.6% than in controls. When the subjects were divided into children (aged 4-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 49 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…We measured serotonin turnover (5HIAA/5HT) and found a significant reduction in cortex from males exposed to PNS when compared with non-stressed controls. In addition, we found a reduction in MAO-A, an enzyme responsible for the breakdown of amines including 5HT, in the cortex of male mice exposed to PNS when compared to non-stressed controls, mirroring what was found in post-mortem tissue of children with ASD who have abnormal social behavior [31]. Together, these data reflect an overall increase in 5HT in the cortex of the male mice exposed to PNS.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We measured serotonin turnover (5HIAA/5HT) and found a significant reduction in cortex from males exposed to PNS when compared with non-stressed controls. In addition, we found a reduction in MAO-A, an enzyme responsible for the breakdown of amines including 5HT, in the cortex of male mice exposed to PNS when compared to non-stressed controls, mirroring what was found in post-mortem tissue of children with ASD who have abnormal social behavior [31]. Together, these data reflect an overall increase in 5HT in the cortex of the male mice exposed to PNS.…”
Section: Discussionsupporting
confidence: 79%
“…In addition, we found that this early life exposure affects cortical 5HT metabolism, elevated markers of neuroinflammation, and oxytocin, as well as corticosterone levels in response to social interaction. This constellation of changes reflects neurobiological changes seen in individuals with ASD [9,31,42,43,5052]. Our findings suggest that the roots of the psychopathology of this disorder may lie in utero, and be connected to aberrant establishment of the Gut-brain-axis.…”
Section: Discussionmentioning
confidence: 51%
“…Changes in the plasma or serum concentrations and genetic variants of synthesizing enzymes, receptors or transporters in both the 5-HT and DA systems have been reported to co-occur in psychiatric disorders. For example, cerebral monoamine oxidase activity that catalyzes the metabolism of monoamine neurotransmitters, such as 5-HT and DA, was significantly lower by 20.6% in autistic groups compared with that in normal controls [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that pre- and postnatal exposure to abnormally high levels of the serotonergic agonist, mimicking the levels observed in autism, induced a significant decrease in the total number of dendritic spines in neurons of the dentate nucleus of rat cerebellum [180]. In addition, analysis of postmortem tissues has revealed a significant impairment in the activity of monoamine oxidases-A (MAO-A), in the cerebellum of children with autism (age 4–12 years) compared to control subjects [181]. Since monoamine oxidases (MAOs) catalyze the metabolism of monoamine neurotransmitters, a reduced MAO-A activity will cause an increase of 5-HT level in the brain of autistic subjects.…”
Section: Discussionmentioning
confidence: 99%